Behavioral Pattern during Dental Pain in Intellectually Disabled Children: A Comparative Study - Shanmugam, Muthukali (Int Sch Res Notices, 2014)
Aim. Children with developmental disabilities generally experience more pain than the normal children. Description of pain is generally difficult in children and more so in children with intellectual disabilities. The study aimed at evaluating dental pain in children with intellectual disabilities. Methods. The survey was carried out in an institution caring for intellectually disabled children to determine the oral health status and the treatment needs of the special kids. 236 children were surveyed out of which the test group is comprised of 111 intellectually disabled children and the control group had 125 normal children with age ranging between five to eighteen years. A questionnaire was presented to the caregivers to elaborate about dental pain in their wards using the dental discomfort questionnaire (DDQ+). The children were examined for dental caries and periodontal status based on the WHO indices for oral hygiene status. Result. Results revealed a statistically significant difference between intellectual disability and brushing, chewing, and earache. The frequency of reporting dental pain was lesser in the intellectually disabled group. Conclusion. Children with intellectual disability tended to report dental pain of any nature with lesser frequency than typically developing peers. They also faced greater difficulty in brushing and chewing.